ANALISIS KINERJA KEUANGAN DENGAN METODE RGEC PADA BANK PEMBANGUNAN DAERAH DI BURSA EFEK INDONESIA - Suwedy Aziz; Muhammad Yunus Kasim; Husna Husna (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
This study aims to analyze the financial performance of publicly listed Regional Development Banks on the Indonesia Stock Exchange for the 2016-2020 period using the descriptive quantitative method. In this study, all populations were the samples or censuses. The results of this study that the financial performance of the Regional Development Bank for the 2016-2020 period is seen from the Risk Profile of the NPL ratio of regional banks BJBR category is very good, BJTM is good and BEKS is quite good, for the LDR ratio of BJTM regional banks in general is still very good, BJBR banks are quite good and BEKS banks are not good. The GCG assessment of BJBR regional banks for the 2016-2020 period is in the good category, BJTM banks in general are still in the good category and BEKS banks are quite good. Earnings, ROA and BOPO ratios of regional banks BJBR and BJTM for the 2016-2020 period are generally very good while BEKS banks are not good. Capital, the CAR ratio of regional banks BJBR and BJTM for the 2016- 2020 period is very good while BEKS banks are still in good condition.